Preservative Treatment of Borak (Bambusa balcooa Roxb.) and Ora (Dendrocalamus longispathus(Kurz.) Kurz.) Bamboo Sticks for Betel Leaf Farms - Rahman, Mohammad Anisur; Akhter, Khurshid; Salam, Abdus; Chowdhury, Mozammel Hoque (Indian Forester, 2018)
Sticks of borak (Bambusa balcooa Roxb.) and ora (Dendrocalamus longispathus (Kurz.) Kurz.) bamboos were treated by soaking methods using water borne preservatives, copper sulphate, sodium dichromate and boric acid (CCB solution). The strips were treated using 5%, 7% and 10% CCB preservatives (2:2:1) aqueous solution by soaking process. The duration of soaking time was 1, 2 and 3 days. The average uptake and retention were measured by weighing the samples before and after the treatment. It was observed that the retention of the preservatives were increased with the increase of time and concentration through the sticks of borak bamboo (B. balcooa Roxb.) and ora bamboo (D. longispathus (Kurz.) Kurz.). After weighing, the samples were split into two portions and penetration was determined by colour test. The extent of penetration of the CCB preservatives in the treated samples were compared with the IS code. It was found that the penetrations of the preservatives were increased with the increase of time through the bamboo sticks. The treated bamboo sticks were distributed to the betel leaf farmers in different areas of Bangladesh. Data were collected after every six months to measure the durability of the bamboo sticks. The preservative treatment technology will expand the service life of the materials and conserve forest resources.